The Charcot-Marie-Tooth Functional Outcome Measure (CMT-FOM). (9th October 2018) - Eichinger, Katy; Burns, Joshua; Cornett, Kayla; Bacon, Chelsea; Shepherd, Mary Lohse; Mountain, Joan; Sowden, Janet; Shy, Rosemary; Shy, Michael E.; Herrmann, David N.
Abstract : Objective: The purpose of this study was to examine the feasibility, reliability, and convergent validity of the Charcot-Marie-Tooth Functional Outcome Measure (CMT-FOM), a new performance-based measure assessing functional ability in adults with CMT disease. Methods: Adults with CMT type 1A (CMT1A) were recruited at the Universities of Rochester and Iowa. Participants were assessed using the CMT-FOM, CMT Exam Score (CMTES), and a symptom report. Test-retest reliability was examined using intraclass correlation coefficients, internal consistency using Cronbach α, and convergent and known-groups validity using Spearman rank analysis and the Mann-Whitney test. Results: Forty-three individuals (70% women; mean age 41, SD 14.9 years) participated. The CMT-FOM (mean 25.3 ± 8.7, range 12–44/52) was moderately correlated with the CMTES (ρ = 0.62; p < 0.0001) and exhibited acceptable reliability (intraclass correlation coefficient = 0.92) and internal consistency (Cronbach α = 0.81). The CMT-FOM discriminated between participants with clinically mild vs moderate-severe CMT1A. Participants with the mildest CMT1A who demonstrated a floor effect on the CMTES showed functional limitations on the CMT-FOM. Conclusions: The CMT-FOM is well tolerated and showed no floor/ceiling effects in an adult CMT1A cohort matching those likely to enter upcoming clinical trials. It appears to be reliable, and our data support convergent and known-groups validity in adults with CMT1A. Longitudinal studies further examining the psychometric properties of the CMT-FOM and its responsiveness to change before its application in therapeutic trials are necessary.